Automorphisms and Inner Automorphisms - Ameer Jaber; Moh’D Yasein (Journal of Mathematics)
Let K be a field of characteristic not 2 and let A=A0+A1 be central simple superalgebra over K, and let ⁎ be superinvolution on A. Our main purpose is to classify the group of automorphisms and inner automorphisms of (A,⁎) (i.e., commuting with ⁎) by using the classical theorem of Skolem-Noether. Also we study two examples of groups of automorphisms and inner automorphisms on even central simple superalgebras with superinvolutions.